2011
DOI: 10.1111/j.1442-2042.2011.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting continence recovery 1 month after radical prostatectomy: Results of a multicenter survey

Abstract: Objectives:To assess the factors associated with continence recovery 1 month after radical prostatectomy (RP) and to identify the correlation between these factors. Methods: In total, 2408 men treated with RP for prostate cancer (PCa) were enrolled in the present multicenter prospective study. Clinical (age, body mass index) and urological (catheterization or transurethral resection of the prostate) records, quality of life (QOL) scores determined using various instruments (including the International Index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
0
23
0
2
Order By: Relevance
“…In a multivariate analysis, Sakai et al [44] reported BNP as the only independent predictor of return to continence at 1 and 3 mo. These results were verified by Gacci et al [13]. However, other variables such as preoperative pelvic floor muscle exercises and preservation of the neurovascular bundles (NVB) may also influence early continence recovery [45, 46].…”
Section: Discussionmentioning
confidence: 64%
“…In a multivariate analysis, Sakai et al [44] reported BNP as the only independent predictor of return to continence at 1 and 3 mo. These results were verified by Gacci et al [13]. However, other variables such as preoperative pelvic floor muscle exercises and preservation of the neurovascular bundles (NVB) may also influence early continence recovery [45, 46].…”
Section: Discussionmentioning
confidence: 64%
“…The likelihood of satisfactory erections after surgery is extremely low in patients with severe ED as measured by IIEF [20,21]. Patients with a higher preoperative IIEF are generally more motivated to achieve satisfactory erectile and sexual function after surgery [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the severity of urinary incontinence often decreases with time after RP [6][7][8], previous studies have demonstrated that 8% to 87% of patients still experience urinary incontinence at six months and 5% to 44.5% remain incontinent at one to two years after surgery [7][8][9][10][11][12]. Moreover, up to 50% of patients report some degree of incontinence two years after RP [3], even after pelvic fl oor muscle exercise intervention.…”
Section: Urinary Incontinencementioning
confidence: 99%
“…The scores range from 5 to 25 [31]. In this index, ED is categorized into fi ve types based on the following scores: severe (5-7), moderate (8)(9)(10)(11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25) [31,32].…”
Section: Sexual Function Questionnairementioning
confidence: 99%